Leverage limits and bank risk: New evidence on an old question - Dong Beom Choi; Michael R. Holcomb; Donald P. Morgan (Federal Reserve Bank of New York, 2018)
The supplementary leverage ratio (SLR) rule recently imposed on the very largest U.S. banks has revived the question of whether banks sidestep such rules by shifting toward riskier, higher-yielding assets. Using difference-in-difference analysis, we find that, after the SLR was finalized in 2014, covered banks shifted their portfolio toward riskier (risk-weighted) assets and higher-yielding securities compared to other large banks not subject to the rule. The shifts are sizable and tend to be larger at banks more constrained ex ante by the leverage limit. Despite increased asset risk, overall bank risk (book and market measures) did not increase, suggesting the higher capital required under the new rule offset the risk-shifting. Taken together, our findings reinforce regulators' long-standing concerns about risk-shifting around leverage limits and suggest that the recent recalibration will curb those incentives without necessarily increasing bank risk.
Keywords: G20; G21; G28; 330; Basel III regulation; bank risk; leverage limit; regulatory arbitrage; reaching for yield